Alteration of pancreatic cancer cell functions by tumor-stromal cell interaction - Hamada, Shin; Masamune, Atsushi; Shimosegawa, Tooru (Frontiers in Physiology, 2013)
Pancreatic cancer shows a characteristic tissue structure called desmoplasia, which consists of dense fibrotic stroma surrounding cancer cells. Interactions between pancreatic cancer cells and stromal cells promote invasive growth of cancer cells and establish a specific microenvironment such as hypoxia which further aggravates the malignant behavior of cancer cells. Pancreatic stellate cells (PSCs) play a pivotal role in the development of fibrosis within the pancreatic cancer tissue, and also affect cancer cell function. PSCs induce epithelial-mesenchymal transition and cancer stem cell (CSC)-related phenotypes in pancreatic cancer cells by activating multiple signaling pathways. In addition, pancreatic cancer cells and PSCs recruit myeloid-derived suppressor cells which attenuate the immune reaction against pancreatic cancer cells. As a result, pancreatic cancer cells become refractory against conventional therapies. The formation of the CSC-niche by stromal cells facilitates postoperative recurrence, re-growth of therapy-resistant tumors and distant metastasis. Conventional therapies targeting cancer cells alone have failed to conquer pancreatic cancer, but targeting the stromal cells and immune cells in animal experiments has provided evidence of improved therapeutic responses. A combination of novel strategies altering stromal cell functions could contribute to improving the pancreatic cancer prognosis.